A Study On The Significant Of Wildlife Crossing Build In Malaysia - Jasme, Amir Akmal; Aiman Samsudin, Muhammad Shamer; Abu Bakar , Syamsul Qamar; Mat Nor, Ahmad Hakimi (Multidisciplinary Applied Research and Innovation, 2022)
Roadkill has become one of the most common sources of wildlife mortality and one of the most serious threats to wildlife. From 2015 to 2019, the Department of Wildlife and National Parks (PERHILITAN) in Peninsular Malaysia reported a total of 2,055 wildlife deaths due to roadkill. According to the data, the number of wild animals killed in road accidents is higher than the number of wild animals killed by illegal hunters. This, however, concern many parties if the situation persists. Researchers believe that one of the most ideal techniques to reducing such incidents is to use Wildlife Crossing. The purpose of this research is to learn more about the background and advantages of building Wildlife Crossings by polling the Malaysian public and research. Animals in the matutinal area are most active in the morning, while those in the vespertine area are most active at nightfall. The study's main goal was to identify peak times and types of animals crossing the road based on the observations of the respondent and to conduct a study on the benefits of wildlife bridges on Malaysian roadways as well. In exchange, survey data on the necessity and need for wildlife crossing construction in Malaysia can be produced at the conclusion of this study. The questionnaire was used to find out when and how often animals cross the road. This is critical in assisting the researcher in better understanding the study and achieving the goals.